2019
DOI: 10.1038/s41598-019-49559-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of upscaling on identification of reservoir fluid properties using seismic-scale elastic constants

Abstract: Elastic constants derived from seismic-scale measurements are often used to infer subsurface petrophysical properties based on rock-physics relationships established from either theoretic model or core-scale measurements. However, the spatial heterogeneity of rock physical properties at the local scale has a significant impact on this relation. To understand this problem, we built a scaled physical model comprised of artificial porous layers with different pore fluids. After conducting a two-dimensional marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several studies have shown the applicability of 3D seismic data for fracture analysis (Jaglan et al, 2015;Fang et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020;Méndez et al, 2020), which can be used to address the often-raised question of scalability of reservoir properties (e.g. Lake & Srinivasan, 2004;Li et al, 2019), i.e., can information regarding fracture properties be transferred from the well scale to the seismic scale and vice versa? To address this question, an adapted seismic fracture orientation analysis (FOA) workflow based on e.g.…”
Section: Ant-track Based Fracture Orientation Analysismentioning
confidence: 99%
“…Several studies have shown the applicability of 3D seismic data for fracture analysis (Jaglan et al, 2015;Fang et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020;Méndez et al, 2020), which can be used to address the often-raised question of scalability of reservoir properties (e.g. Lake & Srinivasan, 2004;Li et al, 2019), i.e., can information regarding fracture properties be transferred from the well scale to the seismic scale and vice versa? To address this question, an adapted seismic fracture orientation analysis (FOA) workflow based on e.g.…”
Section: Ant-track Based Fracture Orientation Analysismentioning
confidence: 99%
“…Several studies have shown the applicability of 3D seismic data for fracture analysis (Jaglan et al, 2015;Fang et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020;Méndez et al, 2020), which can be used to address the often-raised question of scalability of reservoir properties (e.g. Lake and Srinivasan, 2004;Li et al, 2019); i.e. can information regarding fracture properties be transferred from the well scale to the seismic scale and vice versa?…”
Section: Ant-track-based Fracture Orientation Analysismentioning
confidence: 99%